The impact of library use on the academic performance and information literacy skills of undergraduate students of the De La Salle Health Sciences Institute in Dasmariñas City, Cavite - Perez, Joy M.; Obille,Kathleen Lourdes B.; Santos, Yhna Therese P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
Academic libraries are imporatant and integral parts of the teaching, learning and research process. To enhance this role, library standards are created. One of these standards is determining the student learning outcomes. Therefore, this study sought the impact of library use on the student learning through the academic activities and academic performance indicated by General Weighted Average of undergraduate students of the De La Salle Health Sciences Institute in Dasmariñas City, Cavite.
The study was descriptive in nature. The survey method was designed to gather information about existing conditions of the respondents. About 310 undergraduate students were chosen as respondents and they were selected using stratified random sampling. The College Student Experiences Questionnaire (CSEQ) is a free online survey developed at Indiana University's Center for Postsecondary Research and Planning, was adapted by the researcher to determine the library use and academic activities of the students. The item on the last part of the survey questionnaire which is the student learning outcome which is information literacy skills was designed by the researcher based on the Big6TM Skills.
Analysis of Variance (ANOVA) was used to determine the comparison in the impact of library use on the information literacy skills when the respondents are grouped according to college and year level. T-test was used to determine the comparison in the impact of library use and information literacy skills which is [the] dependent variable when the respondents are grouped according to age and gender which is [the] independent variable. Pearson's correlation coefficient was used to determine the relationship of the impact of library use on the information literacy skills of the respondents. Linear regression (or linear correlation) was used to determine the relationships/interactions of information literacy skills to the library use, academic activities, GWA and demographic profile.
The findings of the study are the following: (1) majority of the respondents are Bachelor of Science in Medical Radiation Technology students, second year, between the ages 17-19 and females; (2) the extent of library use of selected undergraduate students has moderate extent of library use in the past 12 months; (3) the extent of information literacy skills of selected undergraduate students are quite bit enough in the past 12 months; (4) the extent of involvement in participating different academic activities of selected undergraduate students in terms of course/active learning are oftentimes participated from simple cognitive activities to higher-level cognitive activities; (5) majority of the respondents has a General Weighted Average of Good which is 85-88; (6) the impact of library use on the information literacy skills has a very small positive effect; (7) there is no significant difference on the information literacy skills according to course, year level, age and gender; and (8) there is a significant relationship on the active or course learning on the General Weighted Average of selected undergraduate students. Meanwhile, there is no significant relationship on the library use, information literacy skills, writing experiences, student-faculty interactions and number of papers read and written on the General Weighted Average of selected undergraduate students. It reveals that active learning has a great impact on General Weighted Average of selected undergraduate students. It reveals that active learning has a great impact on General Weighted Average while the library use has moderately impact on General Weighted Average.
The study recommended the following: For future research, a qualitative research study that interviews student's extent of college experiences for the past 12 months would reveal rich data about the quantities of library usage and information literacy skills. Interviews with student's would record detailed information on the extent of library use and the impact of information literacy skills was most effective. Through closer individual observation, researchers could learn how the students were learning and what their motivations were for changes in library usage behaviors. The data could be used to assess the impact of library use on the information literacy skills. Future studies should examine the factors that influence undergraduates' library use to create resources and services designed to increase students' academic library use. One reason for overall low library use might be that the majority of the use of library services and resources in this study was limited to library used in the library building. A future study that includes remote access to library resources and services such as electronic databases and journals, digital reference, and so forth might result in different findings. Academic library use might actually increase with remote access to these resources and services.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: De La Salle Health Sciences Institute Dasmariñas City, Cavite -- Use studies; Students -- Rating of -- Philippines -- Cavite; Information literacy -- Philippines -- Cavite